Fraud Triangle Perspective on Corruption in State Owned Enterprises: Evidence from the PT Timah, Tbk Case - Ade Irma; Wiend Sakti Myharto (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
Corruption within state-owned enterprises (SOEs) remains a critical challenge in emerging economies, undermining public trust, financial integrity, and investor confidence. This study examines the corruption case of PT Timah Tbk in Indonesia through the lens of Fraud Triangle Theory, focusing on the interaction of pressure, opportunity, and rationalization. Employing a normative juridical approach complemented by literature and documentary analysis, the research analyzes legal frameworks, organizational governance, and empirical evidence related to the case. Findings indicate that financial pressures from market expectations and declining profits created strong motivational drivers (pressure), while weaknesses in corporate governance, procurement procedures, and oversight mechanisms enabled illicit practices (opportunity). Executives rationalized these actions as necessary for achieving corporate targets and preserving organizational interests (rationalization). Legal analysis confirms that these actions violated Law No. 20/2001 on Corruption and Law No. 19/2003 on SOEs, demonstrating gaps between statutory provisions and effective enforcement. The study highlights that addressing SOE corruption requires an integrated strategy combining strengthened internal controls, transparency, ethical leadership, whistleblower protection, and robust legal enforcement. By systematically linking theoretical, legal, and empirical perspectives, this research provides both explanatory insights into corporate fraud mechanisms and practical guidance for enhancing governance and accountability in state-owned enterprises, particularly in resource-based sectors of emerging markets.